Strain-induced reactivation of corrosion pits in austenitic stainless steel. (15th August 2017) - Almuaili, F.A.; McDonald, S.A.; Withers, P.J.; Cook, A.B.; Engelberg, D.L.
Graphical abstract: Highlights: Strain-induced reactivation of a corrosion pit was observed, in-situ. Pit stability products and 3D pit growth kinetics were estimated. Applied strain resulted in diffusivity parameter ( Deff Δ C ) of 4.5 × 10 −8 mol cm −1 s −1 . Lacy metal cover fractures were observed. Abstract: The reactivation of a corrosion pit under the synergetic effect of strain and electro-chemical polarisation has been observed in a type 304L stainless steel using X-ray computed tomography. The pit reactivation process was associated with the formation of a new pit, directly adjacent to a pre-existing pit. Pit growth kinetics were estimated, revealing an increase of the diffusivity parameter ( D eff Δ C ) from 3.0 × 10 −8 mol cm −1 s −1 to 4.5 × 10 −8 mol cm −1 s −1 with the application of strain, indicating higher metal dissolution rates. Applied strain resulted in fractured lacy metal covers, and its effect on pit growth kinetics is discussed.